S. Rahemtulla (2017). Qur’an of the oppressed: Liberation theology and gender justice in Islam. Oxford: Oxford University Press. 295 pp. - Taussig, Sylvie (Estudios de Asia y África, 2020)
S. Rahemtulla (2017). Qur’an of the oppressed: Liberation theology and gender justice in Islam. Oxford: Oxford University Press. 295 pp.